THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT SYAHID AL-IRSYAD AL-ISLAMIYAH HAURGEULIS HOSPITAL, WEST JAVA, INDONESIA - Rukiman, Tupiatman; Saksana, Joned Ceilendra; Upe, Rachman (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This study examines the influence of leadership style and work discipline on employee performance at Syahid Al-Irsyad Al-Islamiyah Haurgeulis Hospital, West Java, Indonesia. Conducted over six months, the research involved 30 active employees selected using a non-probability sampling method. The study aims to understand how these factors individually and collectively impact performance. Data was collected via questionnaires and analyzed using statistical methods. The results indicate that leadership style significantly and positively affects employee performance, with a t-count of 2.656 exceeding the t-table value of 2.062 (p = 0.002). Similarly, work discipline also shows a significant positive effect on performance, with a t-count of 4.067 surpassing the t-table value of 2.062 (p = 0.021). The F-test further supports these findings, showing that the combined influence of leadership style and work discipline on performance is significant (F-count = 9.807 > F-table = 2.69, p = 0.001). These results highlight the importance of effective leadership and strict work discipline in enhancing employee performance. The study's implications suggest that hospital management should focus on these areas to improve overall performance